2011
DOI: 10.4061/2011/127315
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Resistance Training, and Diabetes Prevention

Abstract: With the aging of the baby-boom generation and increases in life expectancy, the American population is growing older. Aging is associated with adverse changes in glucose tolerance and increased risk of diabetes; the increasing prevalence of diabetes among older adults suggests a clear need for effective diabetes prevention approaches for this population. The purpose of paper is to review what is known about changes in glucose tolerance with advancing age and the potential utility of resistance training (RT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 137 publications
(189 reference statements)
0
52
0
1
Order By: Relevance
“…This research also found that muscular strength was inversely associated with the risk of colorectal cancer-specific mortality, although this result was based on very small numbers [8]. Other research suggests that resistance training influences insulin sensitivity, glucose uptake, and diabetes risk [9][10][11][12][13], all of which are thought to play a role in colon carcinogenesis [14,15]. It therefore appears biologically plausible that resistance training may be associated with a reduced risk of colon cancer.…”
Section: Introductionmentioning
confidence: 73%
“…This research also found that muscular strength was inversely associated with the risk of colorectal cancer-specific mortality, although this result was based on very small numbers [8]. Other research suggests that resistance training influences insulin sensitivity, glucose uptake, and diabetes risk [9][10][11][12][13], all of which are thought to play a role in colon carcinogenesis [14,15]. It therefore appears biologically plausible that resistance training may be associated with a reduced risk of colon cancer.…”
Section: Introductionmentioning
confidence: 73%
“…According to subsequent information of 8 weeks resistance training of two groups ( [ 17 ] . It can be deduced from some literature that plasma HDL elevation can lead to weight loss and plasma triglyceride [ 18 , 11 ] that verifies the current research results.…”
Section: Resultsmentioning
confidence: 99%
“…Also it has been shown that these types of exercises are effective for the elderly and obese [ 15 , 16 ] . Some evidence has shown that the intensity variable in resistance exercises is more effective than training volume in treating patients with type 2 diabetes and also it's effective in insulin resistance improvement, metabolic control and cardiac function in these patients [ 17 ] . Elderly people experience significant decrease in strength and muscle mass and also the results of recent studies have shown that Middle-aged people with type 2 diabetes in comparison to healthy people are Face to losing more muscle mass drop muscle quality and increase visceral fat; Therefore, resistance training for these patients is more beneficial]18[ .…”
Section: Introductionmentioning
confidence: 99%
“…10 JS was encouraged to engage in resistance training based on these recommendations, which are supported by research that suggests that resistance training may improve insulin sensitivity and prevent the onset of T2DM with advancing age. 38 …”
Section: Discussionmentioning
confidence: 99%